2013
DOI: 10.1021/ja400229v
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Insights into the Structural and Chemical Changes in Mixed-Anion FeOF Electrodes by Using Operando PDF and NMR Spectroscopy

Abstract: In-depth analysis of operando X-ray pair distribution function (PDF) data is combined with Li NMR spectroscopy to gain comprehensive insights into the electrochemical reaction mechanism of high-performance iron oxyfluoride electrodes. While the full discharge capacity could be recovered upon charge, implying reversibility of the electrochemical reaction, the atomic structure of the electrode formed after cycling (discharge-charge) differs from the pristine uncycled electrode material. Instead, the "active" ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
183
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(199 citation statements)
references
References 35 publications
8
183
0
1
Order By: Relevance
“…In the work by Wiaderek et al 32 , the PDF technique was strengthened by the coupling with solid state NMR technique, that provides further structural and chemical information on active species (i.e. lithium ions and fluorine).…”
Section: Li-ion Battery Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work by Wiaderek et al 32 , the PDF technique was strengthened by the coupling with solid state NMR technique, that provides further structural and chemical information on active species (i.e. lithium ions and fluorine).…”
Section: Li-ion Battery Materialsmentioning
confidence: 99%
“…It is worth to point out that this work represents, in particular, the first example of such kind of in situ PDF measurement. From an experimental point of view, the Authors measured several in situ PDFs during electrochemical discharge-charge cycles whose curves are reported in Figure 7 32 ; in parallel, Figure 8 32 , shows selected PDFs obtained during the first cycle. Similar features and trends can be appreciated and the structural transitions observed during charge and discharge result largely reversible.…”
Section: Li-ion Battery Materialsmentioning
confidence: 99%
“…11 Lithiation induced structural transition to disordered rock-salt has been observed for other materials, such as Li2MoO4, 12 LiVO3 13 and Li1.211Mo 0.467Cr 0.3O2. 14 Disordered rock-salt was also found as intermediate phase during the lithiation reactions of FeOF, 15 Li-and Mn-rich layered materials 16 and spinels. 17 Recent progress in surveying new cathode materials has demonstrated that disordered rock-salt structure is suitable to access high capacity with superior Li + chemical diffusion and rigid host framework.…”
Section: Introductionmentioning
confidence: 99%
“…9 The incorporation of guest anions of high electronegativity into the crystal lattice is found to be an effective strategy to enhance the electrode performance. 13,16 This leads to a conversion reaction at low voltage plateaus and the initial active phase can hardly be recovered. [12][13][14][15] However, the parent crystal symmetry is often altered by introducing guest anions, making it difficult to identify the individual function of anions governing the performance.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Mixed-anion materials have become a new avenue for developing promising candidates with versatile crystal chemistry and physicochemical properties. 16 In contrast, early transition metal compounds with strong metal-ligand bonding (such as vanadium-based oxides and vanadates) are favourable for Li + intercalation reaction without metal-oxygen bond cleavage. Anion partitioning is often observed in mixed-anion materials upon lithiation (such as FeOF, with the formation of separate oxide and fluoride phases) in case of large mismatch in the bonding between metal and different anion ligands.…”
Section: Introductionmentioning
confidence: 99%